A Preliminary Investigation on the Possibility of Developing a Cancer Vaccine Using Snake Venom Components - Ken H Wong; Darren W Sexton; Alireza Mosavi Jarrahi; Sidgi S Hasson (Asian Pacific Journal of Cancer Biology, 2022)
Cancer is a global health concern and is still the leading cause of death worldwide, with 10 million deaths caused, so far, by the disease in 2020. Although there are treatments to treat some cancers and save lives, these treatments do have drawbacks and can cause side effects. Although various anticancer remedies have been discovered using natural products in the past, none of them went into clinical trials. Scientists still looking for alternative agents, within animal products. Recently venom is gaining attention for its anticancer activities. Objective: The present study, therefore, aimed to address the theoretical possibility that people bitten by venomous snakes may also develop prophylaxis, i.e., natural immunity, against cancer. And whether snake venom can be used as a vaccine due to their similarities with potential cancer antigens or not. Method: An immunoinformatic analysis was performed by correlating potential snake venom components’ amino sequence data with different cancer antigens. Results: Initially, our findings showed that while developed countries have low snakebite rates, they also demonstrated high cancer rates, in contrast to that developing countries, where they have high snakebite rates but low cancer rates. In terms of the immunoinformatic approach, ten cancer antigens have various similarities with five snake venom components. While the amino acid sequence alignment demonstrates similarities below 40%, the antigenicity index scores were found to be high. We predict that an immune system activated in snakebite victims may elicit an immune response against similar epitopes expressed on cancer cells. Hence, victims of snake bites may gain natural immunity against cancer. Conclusion: This study reports that non-lethal snakebites may play a vital role in protecting individuals from developing cancer in the future. Although it is a pilot study, such a concept and findings will open doors for future work to address this finding.